Obsessive–compulsive existential type: a dialectical-phenomenological approach - Fukuda, Lívia; Tamelini, Melissa; Messas, Guilherme (Frontiers in Psychology, 2023)
The clinical presentation of obsessive–compulsive patients is characterized by unwanted, intrusive, nonsensical, self-related, and recurrent ideas, thoughts, images, or impulses associated with active compulsive compensations. Under the operational diagnostic criteria adopted by the biological- and cognitive-oriented neopositivist medical paradigm, it is known as “obsessive–compulsive disorder.” However, this paradigm has been criticized for its controversial assumptions, limited methodologies, theoretic biases, and inconsistency in producing practical outcomes. To bypass some of these issues, we propose a complementary approach that draws on and further develops existing psychopathological studies of the obsessive–compulsive anthropological condition based on dialectical phenomenological psychopathology. As such, we refer to the global clinical configuration as the “obsessive–compulsive existential type.” Our theoretical inspiration comes from the classical phenomenological work on obsessions undertaken by Straus and Gebsattel, which identified the negative transformation of the obsessive–compulsive life-world or the endogenous emergence of the anti-eidos (diluting existential force). We then propose to broaden the concept of anti-eidos, especially in its dialectical correlation with eidos (unifying existential force), representing the existential dialectic between transformation and permanence. Next, we detail the dynamics of anthropological disproportions in obsessive–compulsive existential type, essentially the supremacy of the anti-eidos over the eidos. This primary imbalance modifies the obsessive–compulsive existential structure, consisting of polymorphic temporality; weakened intentionality; maladjusted calibration of distance with the world and others; an integral, isolated, besieged self with dwindling self-agency, and tense and over-protecting embodiment. We also analyze compensatory hyperreflexivity and compulsive rituals as expressions of structural counterbalancing designed to contain the primary structural disproportions and derangements. The heterogeneous obsessive–compulsive clinical manifestations are the complex result of the primary structural alteration and subsequent phenomenological compensations. They tend to be variable in temporal span and rarely assume a fixed form, hindering diagnosis. We correlate structural frameworks with multiple clinical examples. Finally, we raise some insights on how our study may contribute to scientific research and therapeutic proposals.